Concentration of Enteric Viruses from Water with Lettuce Extract - Konowalchuk, J. (1974)
A method for recovering enteroviruses, adenovirus, and reovirus from water with lettuce extract is described. Lettuce extract at pH 8.5 was added to the sample and the pH was reduced stepwise with hydrochloric acid to 4.0 to 4.5. The flocculent lettuce-extract particles, and adsorbed virus, were readily removed from solution by low-speed centrifugation. Electron microscopy suggests that, under conditions suitable for adsorption, virus particles are coated with the lettuce-extract colloid.